2014
DOI: 10.1021/am5008694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Au Nanorods on Potential Barrier Modulation in Morphologically Controlled Au@Cu2O Core–Shell Nanoreactors for Gas Sensor Applications

Abstract: In this work, Au@Cu2O core-shell nanoparticles (NPs) were synthesized by simple solution route and applied for CO sensing applications. Au@Cu2O core-shell NPs were formed by the deposition of 30-60 nm Cu2O shell layer on Au nanorods (NRs) having 10-15 nm width and 40-60 nm length. The morphology of Au@Cu2O core-shell NPs was tuned from brick to spherical shape by tuning the pH of the solution. In the absence of Au NRs, cubelike Cu2O NPs having ∼200 nm diameters were formed. The sensor having Au@Cu2O core-shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 48 publications
1
53
0
Order By: Relevance
“…2 (d (101) = 0.2475 nm). In the particle region, an interlayer spacing of 0.232 nm was obtained, complying with the lattice spacing of (1 1 1) planes of the fcc Au [39]. The average sizes of the Au nanoparticles are about 10-20 nm.…”
Section: Structural and Morphological Characteristicssupporting
confidence: 63%
See 1 more Smart Citation
“…2 (d (101) = 0.2475 nm). In the particle region, an interlayer spacing of 0.232 nm was obtained, complying with the lattice spacing of (1 1 1) planes of the fcc Au [39]. The average sizes of the Au nanoparticles are about 10-20 nm.…”
Section: Structural and Morphological Characteristicssupporting
confidence: 63%
“…Generally, the gold plays two important roles in increasing the gas sensing properties. Firstly, because the work function of Au (5.1 eV) is larger than ZnO (3.3 eV), the electrons in ZnO will transfer to Au leading to the Schottky barrier and an addition depletion layer at the interface[39,47]_ENREF_40. The conduction channel of Au decorated flower-like ZnO microstructures is much narrower compared with pure ZnO.…”
mentioning
confidence: 99%
“…Compared with spherical or nearly spherical Au cores, Au nanorods can support transverse and longitudinal LSPR modes, offering a better tunability of the LSPR wavelength and higher controllability of the optical response through the polarization state of the excitation light . However, there have been only a few reports on coating Cu 2 O on Au nanorods, most of which have focused on the effects of the refractive index and thickness of the Cu 2 O shell on the plasmon resonance shift. How the morphology and structure of the interface between the Au nanorod core and Cu 2 O shell affect the plasmon resonance has so far remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Some techniques have been developed to enhance the sensing performance, including morphological control, 7-9 heterostructure formation and metal nanoparticles modifying. [10][11][12][13][14] Yang et al found that Cu/Cu x O nanoarchitectures showed e®ective detection to NO x . 10 At the same time, Sonawane et al studied the e®ects of Cu doping on good gas sensing properties.…”
Section: Introductionmentioning
confidence: 99%